Validity and reliability of single camera markerless motion capture systems with RGB-D sensors for measuring shoulder range-of-motion: a systematic review - Lee, Unhyung; Lee, Suji; Kim, Sung-A; Kim, Yohwan; Lee, Seunghoon (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAssessing shoulder joint range-of-motion (ROM) is crucial for evaluating shoulder mobility but remains challenging due to its complexity. This review examined the potential of single-camera markerless motion capture systems with an RGB-depth (RGB-D) sensor for shoulder ROM measurements, focusing on their reliability and validity.MethodsWe systematically searched nine databases through December 2022 for studies that evaluated the reliability and validity of single-camera markerless motion-capture systems in measuring simple (one-directional) and complex (multi-directional) shoulder movements. We extracted data on participant characteristics, device details, and measurement outcomes, and then assessed the methodological quality using the Consensus-Based Standards for the Selection of Health.ResultsOf the 2,976 articles identified, 14 were included in this review. The findings indicate that intra-rater reliability findings across six studies were inconsistent, with simple movements like abduction and flexion demonstrating better reliability and less heterogeneity compared to complex movements. Validity assessments across 12 studies also showed inconsistency, with abduction and flexion measurements exhibiting higher validity than rotational movements. Studies focusing on simple movements reported good to excellent validity, particularly for abduction and flexion. Quality assessments using the COSMIN checklist revealed that the methodological quality varied across studies, ranging from inadequate to very good.DiscussionThis systematic review suggests that RGB-D sensors show promise for measuring shoulder joint ROM, especially in simple movements like flexion and abduction. However, complex movements and inconsistencies limit their immediate clinical applicability, necessitating further high-quality research with advanced devices to ensure accurate and reliable assessments.